AMALPI TREK - Dal Maloja al Gottardo Alpi in Movimento - Movimento nelle Alpi - Apuani, Tiziana; Scapozza, Cristian (Milano University Press, 2023)
AMALPI Trek is a cross-border geotouristic trail that, from the Maloja Pass to the Gotthard region, leads along ancient and new routes, with their natural and anthropic peculiarities (waterfalls, villages), historical-archaeological (such as the excavations in Piuro) and gastronomic (such as foods prepared in soapstone pots, "lavecc"), to discover the processes that drastically change the Alpine territory: the great landslides of the past, present and future. The guidebook allows anyone to enjoy in another way the beauty of the crossed valleys, perhaps walking only short distances, or reaching them by other transportation means (preferably public or zero emissions), relying on interpretations provided by scholars, to understand the landscape evolution and the history of landslides. The hope is to help in promoting a new curiosity towards mountains and what animates them, landslides, increasing the risk awareness in the Alpine environment.